Republic of Belarus : 2007 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Belarus. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This 2007 Article IV Consultation highlights that Belarus's centralized economy grew rapidly over the past few years, enhancing social development. The state redistributed large and growing terms-of-trade gains stemming from favorable Russian energy pricing across the economy, boosting domestic demand. A new energy agreement, however, has abruptly reversed terms-of-trade gains. Belarus now pays Russia twice as much for gas supplies as in 2006 and a fifth more as a share of world market prices for crude oil. This resulted in an estimated loss of 5 1\2 percent of GDP in 2007.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet